2018
DOI: 10.18590/euscorpius.2018.vol2018.iss269.1
|View full text |Cite
|
Sign up to set email alerts
|

Notes on the Genera Buthacus, Compsobuthus, and Lanzatus with Several Synonymies and Corrections of Published Characters (Scorpiones: Buthidae)

Abstract: Euscorpius is the first research publication completely devoted to scorpions (Arachnida: Scorpiones). Euscorpius takes advantage of the rapidly evolving medium of quick online publication, at the same time maintaining high research standards for the burgeoning field of scorpion science (scorpiology). Euscorpius is an expedient and viable medium for the publication of serious papers in scorpiology, including (but not limited to): systematics, evolution, ecology, biogeography, and general biology of scorpions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…One of the important characters distinguishing the species of Lychas is the number of outer and inner denticles along the sixth row of denticles on the movable finger of pedipalp. Unfortunately, Lourenço has repeatedly described and illustrated this character incorrectly (see also Kovařík, 2018). According to his figure 12 in the original description (Lourenço, 2011: 322), the holotype of L. kaimana has the sixth row of denticles on the movable finger of pedipalp without any outer and inner denticles, and the entire row is abnormally irregular.…”
Section: Taxonomic Position Of Lychas Kaimana Lourenço 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the important characters distinguishing the species of Lychas is the number of outer and inner denticles along the sixth row of denticles on the movable finger of pedipalp. Unfortunately, Lourenço has repeatedly described and illustrated this character incorrectly (see also Kovařík, 2018). According to his figure 12 in the original description (Lourenço, 2011: 322), the holotype of L. kaimana has the sixth row of denticles on the movable finger of pedipalp without any outer and inner denticles, and the entire row is abnormally irregular.…”
Section: Taxonomic Position Of Lychas Kaimana Lourenço 2011mentioning
confidence: 99%
“…These analyses demonstrated that some genera of Buthidae are paraphyletic, and in order to maintain monophyly, additional genera should be established. Recently, we diagnosed new buthid genera Barbaracurus Kovařík et al, 2018, Teruelius Lowe & Kovařík, 2019, and Trypanothacus Lowe et al, 2019, by identifying consistent differences in previously overlooked characters.…”
Section: Introductionmentioning
confidence: 99%
“…As already mentioned in prior publications, B. buettikeri does not fit the revised diagnosis of Buthacus, specifically in the shape of the telson (cf. Kovařík et al, 2016b;Kovařík, 2018). We also describe under the new genus a new species T. barnesi sp.…”
Section: Introductionmentioning
confidence: 97%
“…Lourenço (2006) again revised the genus and expressed opposing opinions on the validity of some species. Over the years, new species were individually added, while others were shuffled in or out of synonymy (e.g., Lourenço, 2006;Lourenço & Qi, 2006;Lourenço & Leguin 2009;Kovařík et al, 2016b;Kovařík, 2018). However, beyond nomenclatural issues at the species level, a broader effort is needed to understand and clarify the scope of the genus.…”
Section: Introductionmentioning
confidence: 99%
“…This species, which may in future need to be divided into several species, was first described byHemprich and Ehrenberg (1828) and Ehrenberg (1829) as Androctonus (Leiurus) leptochelys. The status of the genus Buthacus was confusing, but has recently been subject to several revisions (e.g Kovařík 2018;Cain et al 2021)…”
mentioning
confidence: 99%